Variability of ²²²Rn in the sandy aquifer of Buenos Aires coast - Carretero, Silvina Claudia (2021)
²²²Rn is widely used as a tracer to detect and calculate submarine groundwater discharge in coastal zones, rivers and lakes. Relatively few investigations, however, have used this element for other applications in hydrogeology. We analyze the relationship between ²²²Rn activity in groundwater and variations in the water cycle in the sandy aquifer of Buenos Aires coast, Argentina. Groundwater levels, electrical conductivity and ²²²Rn activity were measured in situ in wells in March 2016 and November 2018, representing two different hydrological conditions. Groundwater flow maps were drawn, hydrological gradients and flux velocities were calculated. An inverse correlation between ²²²Rn activity and recharge conditions was found. Lower water surplus shows higher ²²²Rn activity and vice versa, potentially due to dilution of high ²²²Rn activity water with ‘newer’ lower activity recent recharge. A variability in ²²²Rn spatial distribution was identified along the sand dune barrier. A correlation between ²²²Rn and groundwater electrical conductivity was not observed.